2006
DOI: 10.3844/ajabssp.2006.22.26
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Population In Decompsing Legume Litter Of Differing Quality

Abstract: Abstract:The influence of litter quality on microbial population during decomposition of fresh pruning of Acacia auriculiformis; Gliricidia sepium and Acacia mixed with Gliricidia (50 : 50) is reported. Acacia (soluble C, 46.6%; N, 3.9%; Phenolic, 2.3%) was rated as low quality litter while Gliricidia (soluble C, 45.2%; N, 4.8%; Phenolic, 2.3%) was rated as high quality litter. Acacia mixed with Gliricidia (50 : 50) had an initial phase of rapid decomposition followed by a second phase of comparatively lower d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This finding was in accordance with Poll et al (2008), who found that an increase in fungi was detected between 2 and 4 weeks after litter application, based on ergosterol measurements. On the one hand, high proportions of fungi might have been introduced into the system with the plant litter, because most of the litter‐degrading microorganisms were already present on the fresh plant litter (Oyun et al , 2006). On the other hand, the results may indicate that a shift in the microbial community was already occurring due to an increasing complexity of the available substrate after 4 weeks (Poll et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was in accordance with Poll et al (2008), who found that an increase in fungi was detected between 2 and 4 weeks after litter application, based on ergosterol measurements. On the one hand, high proportions of fungi might have been introduced into the system with the plant litter, because most of the litter‐degrading microorganisms were already present on the fresh plant litter (Oyun et al , 2006). On the other hand, the results may indicate that a shift in the microbial community was already occurring due to an increasing complexity of the available substrate after 4 weeks (Poll et al , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…These results are in contrast to many studies where litter degradation in well‐developed soil ecosystems has been investigated. In most of these studies, a clear increase of fungal biomass over time has been described (Aneja et al , 2006; Oyun et al , 2006; Williams et al , 2006). Obviously, fungi are highly dependent on N; hence, as in our study, N was limited in soil, there was a need to use plant‐derived N. The low amounts of available N in C. epigejos litter material after 12 weeks and in both litter types after 40 weeks might therefore explain the reduced fungal biomass, from which Gram‐positive bacteria could benefit.…”
Section: Resultsmentioning
confidence: 99%
“…Mixtures of residues from different species have chemical characteristics intermediate to those of their component species alone [23,25,38], and this has been specifically observed in grass-legume mixtures [43,44]. In addition, Andriulo and Cordone [45] and Ernst et al [34] found insoluble fiber concentrations very similar between soybean and maize residues.…”
Section: Compounds Of Residues Mixturesmentioning
confidence: 99%
“…Consequently, as suggested by Mao and Zeng [22], residue decomposition dynamics in agroecosystems should be assessed on the basis of residue mixtures for a better understanding and management of nutrient dynamics. Despite these considerations, the broad majority of studies in agroecosystems have focused on decomposition and nutrient dynamics of single or _more scarcely_ mixed fresh residues [4,15,[23][24][25]. However, information about the decomposition of realistic crop residues mixtures in NT systems (i.e., mixtures of residues with different decomposition degree) or its contribution to crops nutrition and soil fertility is very scarce [2,26,27].…”
Section: Introductionmentioning
confidence: 99%